A new type of rotating working machine with one leader and one complementary rotor - Constant, Mihaela; Băran, Nicolae; Tănase, Beatrice; Donisan, Evelina (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
A new constructive solution of a working machine which is simpler and has a higher reliability in comparison with other solutions is presented. The computation relations of the driving power and the flow rate for the rotating working machine are deducted; this machine can function as a pump, fan or low pressure compressor. Any pure fluid substance or with suspensions is circulated from suction to discharge by a rotor with two profiled pistons